Kissing the Chimney: Managing a Protuberant Coronary Stent During Transcatheter Aortic Valve Replacement. (November 2021) - Khurana, Ayush; Obaid, Daniel; Chase, Alexander; Smith, David
Abstract : Supplemental Digital Content is available in the text.